Studi Literatur Pengaruh Sistem Pre-Order dalam Penyusunan Anggaran Produksi Perusahaan - Angel Sri Monika Sijabat; Ferdy Faith Christ Waruwu (Perkumpulan Konsultan Manajemen Pendidikan Indonesia (PKMPI), 2026)
Production budgeting is an important aspect of a company's operational activities because it is closely related to production planning, cost control, and resource management. Inaccurate demand forecasting may result in overproduction or underproduction, which can increase operational costs and reduce company efficiency. One strategy that can be implemented to overcome this problem is the pre-order system, which is a production system based on customer orders before the production process begins. This study aims to analyze the influence of the pre-order system on the preparation of production budgets through a literature review approach. The research method used in this study is a literature review with a descriptive qualitative approach. The data were obtained from various journals, scientific articles, books, and academic references related to the pre-order system, production planning, and production budgeting. The results of the study indicate that the pre-order system helps companies improve the accuracy of production budgeting because production quantities are adjusted to actual customer demand. In addition, the pre-order system also helps companies reduce raw material waste, minimize inventory storage costs, improve resource efficiency, and maintain cash flow stability. Therefore, the pre-order system can be considered an effective strategy in supporting more efficient, realistic, and market-oriented production budgeting.